Ketentuan Hukum Kewarisan Bagi Anak Angkat dalam Perspektif Kompilasi Hukum Islam dan Kitab Undang-Undang Hukum Perdata - Hasbiyallahul Muttaqin; Agus Supriyanto (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
The purpose of this study was to determine the inheritance law provisions adopted by the foster child according to Islamic law and the Indonesia Private Law/Burgerlijk Wetboek (KUHPerdata)? This research is descriptive because trying to describe or explain about the relationship and application of inheritance adopted. Data collection tools used in the form of documentation studies, because the data source is obtained from a document in the form of books and scientific findings related to this issue. In the data analysis, the method used is the comparative method. The conclusion of this study that in the Compilation of Islamic Law (KHI) have been assigned the institution was borrowed, that is to say, the adoptive parents it does not give the inheritance to his adopted son, but he get through was borrowed as much as a third of the property heritage adoptive parents and the biological parents he remained as heir. Meanwhile, according to Indonesia Private Law/Burgerlijk Wetboek adopted child could inherit the estate adoptive parents unanimously (legitieme portei).